Assessing Planulae Recruitment in Degraded Coastal Coral of Panjang Island Jepara, Central Java-Indonesia - Afiati, Norma; Purnomo, Pujiono W. (Innovations in Biological Science Vol. 7, 2024)
The successfulness of planulae metamorphosis to become juveniles commenced succession toward the formation of a new coral community following stress. The better the remnant, the more similar the recovered community will be. Coral remnants may provide attachment preference for benthic organisms including its planulae and indeed serve as a nursery ground, even a habitat for various species. This study aimed to evaluate the recovery of the coastal coral community in Panjang Island, Jepara-Indonesia based upon several variables of water quality, recruitment through the succession stages, survivorship and the overall growth of the coral. During the first week of June 2013 until the end of October 2013 after a west monsoon, six slate collector devices were immersed between the slope and plain of the continental shelf at the north, south and eastward of Panjang Island at ca. 1.5 m depths. Data collected comprised of bacteria, macro- and micro-periphyton including planulae, along with salinity, temperature, depth, turbidity, dissolved oxygen, orthophosphate and nitrate of the water, as well as inorganic and organic content of the sediment. Recorded genera in the collectors were Porites, Acropora, Pocillopora and Platygira. Results suggested that coastal coral in Panjang Island is inclined to extinct, in particular, due to severe sedimentation load. Planulae recruit considered low with metamorphosis ability to become juveniles only at 5 colonies. M2. Month-1 at the southward and 1.3 colonies. m-2 . Month-1 at the northward of the island. Dissolved organic materials in the sediment prompt the increase of nitrate to cause macroalgal bloom, which in turn may cover the whole coral surface and induce the spread of pathogenic bacteria, i.e., Pseudomonas spp. and Phormidium corallyticum amongst the recruited planulae. It can be concluded that factors causing difficulties in recovering coral in Pulau Panjang, in particular planulae recruit are: 1) physical damage due to coastal development and tourism-related activities, 2) pollution and runoff from urban areas nearby, 3) agricultural activities that introduce pollutants such as chemicals and sedimentation, and 4) coral diseases that may decrease resilience to other stressors. Addressing these factors through conservation efforts, sustainable management practices and law enforcement may help protect and restore damaged coastal corals in Panjang Island.